2(y-4)+5=3(y+2)
multiply the first bracket by 2
(2)(y)=2y
(2)(-4)=-8
multiply the second bracket by 3
(3)(y)=3y
(3)(2)=6
2y-8+5=3y+6
2y-3=3y+6
move 3y to the other side
sign changes from +3y to -3y
2y-3y-3=3y-3y+6
-y-3=6
move -3 to the other side
-y-3+3=6+3
-y=9
multiply both sides by -1 to get +y
(-1)(-y)=9(-1)
Answer:
y=-9
The equal of x+7=26 so it’s definitely (a)
First bring 3x to the other side, which will give you -2y= -16-3y. Then divide everything by -2, which will give you y=8+3/2x
D. Hope that is the answer